Fundamentos teórico-metodológicos para la planificación ambiental del turismo en paisajes sensibles - Del Risco Yera, Y.; Acevedo Rodríguez, P. (Geographicalia, 2016)
Proposals of elements to achieve the environmental planning of the tourist activity in sensitive landscape. To do this the task of the inventory, analysis, evaluation, diagnosis, presage and design of the landscapes of the area were carried out to obtain the fundamental characters of their structure and operation; the evaluation of the potentials, the diagnosis of the state, the degradation and the environmental problems and the prediction of the behaviour of the different possible scenarios were also taken into account. Based on all these aspects the basic elements of the design of the landscape with a view of the environmental planning were proposed.
Keywords: environment; tourism; landscape; ecological management.